Hubungan antara Jenis Promosi dan Tingkah Laku Pembelian dalam Talian - Yi hui, Chin; Shahrul Nizam Salahudin, (Research in Management of Technology and Business, 2024)
This study aims to analyze the relationship between promotion type and online purchasing behavior. In the increasingly developing digital era, online promotion is an important marketing strategy for companies to attract attention and encourage consumers to purchase online. Therefore, it is important to understand how promotion type affects online purchasing behavior. This study combines relevant literature and empirical research to explore the influencing factors of the relationship between promotion types and online purchasing behavior. This study used quantitative analysis. Using online Google form, a total of 384 questionnaires were collected and distributed to Johor Bahru residents. Data were collected and examined using the Statistical Package for the Social Sciences (SPSS), resulting in a response rate of 75%. According to the results of analysis regression, buy one free one is the main factor for online shopping among Johor Bahru residents. The results of the study showed that there is a significant relationship between discount price, coupon, buy one free one, and free sample. Limitations of this study include uses a simple sampling method where the results of the analysis cannot be concluded to any other population and small sample size. This study provides some suggestions for future research.